Poledenodobni razvoj navadne jelke (Abies alba Mill.) na ozemlju današnje Slovenije - Brus, Robert (Zbornik gozdarstva in lesarstva, 2009)
The paper reviews the research dealing with the presence of silver fir (Abies alba Mill.) within modern-day Slovenian territory in the Pleistocene and Holocene. The data on paleobotanical remains (Tertiary fossil remains, pollen,macroscopic plant remains) on Paleolithic sites and on genetic properties of the present silver fir populations are presented. The possible existence of glacial refugia and local postglacial development of silver fir populations in Slovenia are discussed.
Keywords: Abies alba Mill.; genetska variabilnost; ledenodobna zatočišča; navadna jelka; Slovenia; Slovenija